Pengaruh ENSO terhadap Curah Hujan di Sulawesi Tengah - Rangga, Imron Ade; Zuhrita, Annisa; Zalsabilah, Putri (Buletin GAW Bariri (BGB), 2025)
The El Nino – Southern Oscillation (ENSO) has an influences rainfall variability in Central Sulawesi. This study aims to analyze the relationship between ENSO, measured using the Oceanic Nino Index (ONI), and rainfall anomalies at four observation locations: Stamet Luwuk, Poso, Toli – Toli, and Palu. Rainfall data were obtained from BMKG meteorological station observations, while ONI data were sourced from the Climate Prediction Center (CPC) for the period 1991–2024. Analysis was conducted using Pearson correlation and the coefficient of determination to assess the relationship between ENSO and rainfall anomalies. The study results indicate that, in general, El Nino tends to cause a decrease in rainfall, whereas La Nina is often associated with increased rainfall. However, the influence of ENSO is not uniform across all regions and largely depends on its intensity. A relatively strong negative correlation was found in Stamet Toli – Toli and Palu, whereas in Luwuk and Poso, other factors such as local atmospheric variability and intraseasonal phenomena played a more dominant role in determining rainfall patterns. Strong and Very Strong El Nino events have a more significant impact on reducing rainfall, while La Nina exhibits a more varied pattern of influence.